2013
DOI: 10.3109/19396368.2012.751463
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and reproductive outcomes in mice treated with cyclophosphamide in pre-pubertal age

Abstract: Disruption in the normal timing of female puberty, such as in pre-pubertal cancer treatments, can cause abnormal somatic development. We sought to evaluate the impact of cyclophosphamide (CTX) on the somatic, uterine, and ovarian, development of pre-pubertal mice. Pre-pubertal (day 18 of life) C57BL/ 6J female mice were randomized to receive placebo (group 1A and 1B), 200 mg/kg CTX (group 2A), or 120 mg/kg CTX (group 2B). Mice were euthanized on day 56 (A groups) or 95 (B groups) of life. Body weight and lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
3
5
1
Order By: Relevance
“…This confirms our previous findings [7]. These figures are higher than what has been reported in human studies [15,22,23] and it is probably due to the different assessment methods of ovarian function in those studies (presence or absence of puberty or menses) compared to ours (serologic concentrations of AMH and FSH).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This confirms our previous findings [7]. These figures are higher than what has been reported in human studies [15,22,23] and it is probably due to the different assessment methods of ovarian function in those studies (presence or absence of puberty or menses) compared to ours (serologic concentrations of AMH and FSH).…”
Section: Discussionsupporting
confidence: 90%
“…We previously classified the degrees of damage into three main categories (normal FSH, DOR, and POI) by serum FSH values [7]. However, in the current study we unified DOR and POI under the category 'ovarian insufficiency' and found that the histological damage to the ovary was identified by equally low AMH serum levels.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We confirmed that CTX treatment impairs both long bone growth and bone mass accrual, yet with no observable effect on adult body length and weight, as we previously found [Detti et al 2013]. In addition, CTX treatment in pre-pubertal mice appears to negatively affect uterine development.…”
Section: Discussionsupporting
confidence: 90%
“…We previously described the deleterious effects of uterine and femur development after CTX exposure and corroborated those results with hormone serum levels; FSH levels were elevated in exposed mice compared to controls as a function of the development of acute ovarian failure [Detti et al 2013]. Reproductive function of treated mice was previously assessed by others [Meirow et al 2001], who found decreased fertility and an increased miscarriage/malformation rate.…”
Section: Introductionsupporting
confidence: 63%